Magnetic resonance imaging of neuroinflammation in chronic pain: a role for astrogliosis?. Issue 7 (July 2020) - Jung, Changjin; Ichesco, Eric; Ratai, Eva-Maria; Gonzalez, Ramon Gilberto; Burdo, Tricia; Loggia, Marco L.; Harris, Richard E.; Napadow, Vitaly
Abstract : Abstract: Noninvasive measures of neuroinflammatory processes in humans could substantially aid diagnosis and therapeutic development for many disorders, including chronic pain. Several proton magnetic resonance spectroscopy ( 1 H-MRS) metabolites have been linked with glial activity (ie, choline and myo-inositol) and found to be altered in chronic pain patients, but their role in the neuroinflammatory cascade is not well known. Our multimodal study evaluated resting functional magnetic resonance imaging connectivity and 1 H-MRS metabolite concentration in insula cortex in 43 patients suffering from fibromyalgia, a chronic centralized pain disorder previously demonstrated to include a neuroinflammatory component, and 16 healthy controls. Patients demonstrated elevated choline (but not myo-inositol) in anterior insula (aIns) ( P = 0.03), with greater choline levels linked with worse pain interference ( r = 0.41, P = 0.01). In addition, reduced resting functional connectivity between aIns and putamen was associated with both pain interference (whole brain analysis, pcorrected < 0.01) and elevated aIns choline ( r = −0.37, P = 0.03). In fact, aIns/putamen connectivity statistically mediated the link between aIns choline and pain interference ( P < 0.01), highlighting the pathway by which neuroinflammation can impact clinical pain dysfunction. To further elucidate the molecular substrates of the effects observed, we investigated how putative neuroinflammatory 1 H-MRS metabolites are linked with ex vivo tissue inflammatory markers in a nonhuman primate model of neuroinflammation. Results demonstrated that cortical choline levels were correlated with glial fibrillary acidic protein, a known marker for astrogliosis (Spearman r = 0.49, P = 0.03). Choline, a putative neuroinflammatory 1 H-MRS-assessed metabolite elevated in fibromyalgia and associated with pain interference, may be linked with astrogliosis in these patients. Abstract : Supplemental Digital Content is Available in the Text. 1 H-MRS-assessed anterior insula choline levels were elevated in fibromyalgia patients and linked to pain interference. A primate neuroinflammation model linked 1 H-MRS choline levels with astrogliosis.